Decreased ceramide underlies mitochondrial dysfunction in Charcot‐Marie‐Tooth 2F. Issue 3 (3rd January 2018) - Schwartz, Nicholas U.; Linzer, Ryan W.; Truman, Jean‐Philip; Gurevich, Mikhail; Hannun, Yusuf A.; Senkal, Can E.; Obeid, Lina M.
Abstract : Charcot‐Marie‐Tooth (CMT) disease is the most commonly inherited neurologic disorder, but its molecular mechanisms remain unclear. One variant of CMT, 2F, is characterized by mutations in heat shock protein 27 (Hsp27). As bioactive sphingolipids have been implicated in neurodegenerative diseases, we sought to determine if their dysregulation is involved in CMT. Here, we show that Hsp27 knockout mice demonstrated decreases in ceramide in peripheral nerve tissue and that the disease‐associated Hsp27 S135F mutant demonstrated decreases in mitochondrial ceramide. Given that Hsp27 is a chaperone protein, we examined its role in regulating ceramide synthases (CerSs), an enzyme family responsible for catalyzing generation of the sphingolipid ceramide. We determined that CerSs colocalized with Hsp27, and upon the presence of S135F mutants, CerS1 lost its colocalization with mitochondria suggesting that decreased mitochondrial ceramides result from reduced mitochondrial CerS localization rather than decreased CerS activity. Mitochondria in mutant cells appeared larger with increased interconnectivity. Furthermore, mutant cell lines demonstrated decreased mitochondrial respiratory function and increased autophagic flux. Mitochondrial structural and functional changes were recapitulated by blocking ceramide generation pharmacologically. These results suggest that mutant Hsp27 decreases mitochondrial ceramide levels, producing structural and functional changes in mitochondria leading to neuronal degeneration.—Schwartz, N. U., Linzer, R. W., Truman, J.‐P., Gurevich, M., Hannun, Y. A., Senkal, C. E., Obeid, L. M. Decreased ceramide underlies mitochondrial dysfunction in Charcot‐Marie‐Tooth 2F. FASEB J. 32, 1716‐1728 (2018). www.fasebj.org